Association between gut microbiota and gastrointestinal cancer: a two-sample bi-directional Mendelian randomization study - Su, Qing; Jin, Chen; Bo, Zhiyuan; Yang, Yi; Wang, Jingxian; Wang, Juejin; Zhou, Junxi; Chen, Yaqing; Zeng, Hao; Chen, Gang; Wang, Yi (Frontiers in Microbiology, 2023)
Background: The gut microbiome is closely related to gastrointestinal (GI) cancer, but the causality of gut microbiome with GI cancer has yet to be fully established. We conducted this two-sample mendelian randomization (MR) study to reveal the potential causal effect of gut microbiota on GI cancer. Materials and Methods: Summary-level genetic data of gut microbiome were derived from the MiBioGen consortium and the Dutch Microbiome Project. Summary statistics of six GI cancers were drawn from UK Biobank. Inverse-variance-weighted (IVW), MR-robust adjusted profile score (MR-RAPS), and weighted-median (WM) methods were used to evaluate the potential causal link between gut microbiota and GI cancer. In addition, we performed sensitivity analyses and reverse MR analyses. Results: We identified potential causal associations between 21 bacterial taxa and GI cancers (P-values < 0.05 in all three MR methods). Among them, phylum Verrucomicrobia (OR: 0.17, 95% CI: 0.05-0.59, P = 0.005) retained a strong negative association with intrahepatic cholangiocarcinoma after the Bonferroni correction, whereas order Bacillales (OR: 1.67, 95% CI: 1.23-2.26, P = 0.001) retained a strong positive association with pancreatic cancer. Reverse MR analyses indicated that GI cancer was associated with 17 microbial taxa in all three MR methods, among them, a strong inverse association between colorectal cancer and family Clostridiaceae1 (OR: 0.91, 95% CI: 0.86-0.96, P = 0.001) was identified by Bonferroni correction. Conclusion: Our study implicates the potential causal effects of specific microbial taxa on GI cancer, potentially providing new insights into the prevention and treatment of GI cancer through specific gut bacteria.